2020
DOI: 10.1080/19476337.2019.1702104
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds and antioxidant capacity of tea infusion prepared from whole and ground medicinal herb parts

Abstract: This study was conducted to analyze bioactive compounds and the in vitro antioxidant capacity of tea infusions from whole and ground medicinal herbs, including cardamom, cinnamon, clove, nigella, and ginger. Samples of whole medicinal herbs were ground to pass through a 40 mesh (425 µm) sieve, and hot water (95°C) infusions of whole and ground herb parts were examined. Higher bioactive compounds such as phenolic compounds and flavonoids were found in the ground tea infusions. Among the medicinal herb samples, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…The diffusion of phenols, and in particular of oleuropein as the main phenol, to the infusion water was greater as the degree of grinding was lower. Islam et al [29] also observed a higher polyphenol concentration in the infusions when medicinal herbs (cardamom, cinnamon, clove, nigella, and ginger) were ground compared to whole herbs. Alsaud and Farid [30] reported that the extraction of biocompounds of Manuka leaves was faster when a fine powder was employed and indicated that the release of bioactive compounds occurred during grinding.…”
Section: Resultsmentioning
confidence: 92%
“…The diffusion of phenols, and in particular of oleuropein as the main phenol, to the infusion water was greater as the degree of grinding was lower. Islam et al [29] also observed a higher polyphenol concentration in the infusions when medicinal herbs (cardamom, cinnamon, clove, nigella, and ginger) were ground compared to whole herbs. Alsaud and Farid [30] reported that the extraction of biocompounds of Manuka leaves was faster when a fine powder was employed and indicated that the release of bioactive compounds occurred during grinding.…”
Section: Resultsmentioning
confidence: 92%
“…: Lauraceae Local name: Cinnamon 1.2 gm powder of the dried bark is taken in 100 ml hot water (95 °C for 3 min), filtered, and the infusion is used to treat diabetes ( Islam et al, 2020 ). β-carotene, phenolics, and flavonoids are the main bio-active ingredients ( Islam et al, 2020 ). The oral administration of bark powder of C. verum has anti-diabetic properties ( Adisakwattana et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…De acuerdo con la figura 7, se muestran los efectos medicinales encontrados en diferentes plantas herbáceas que han sido utilizados para infusiones, identificándose así con mayor frecuencia los antioxidantes (28.05%), antiinflamatorias (17.07%) y antidiabéticas (9.76%) siendo usadas para contrarrestar algunos daños originados en el cuerpo humano tanto celulares, inflaciones y niveles de glucosa dentro de la sangre. Teniendo esto en cuenta, [33], [17], [19], [34], [35], [36] y [21] mencionaron que la mayoría de las plantas estudiadas en su campo como el clavo, cola de caballo, hierba luisa, cuphea calophylla, hojas de moringa, romero, granada y tomillo de naranja, se consume más en infusiones por sus efectos antioxidantes y antiinflamatorias ya que desempeñan actividades funcionales para contrarrestar diversas enfermedades como muestra en la figura 8.…”
Section: Aprovechamiento Las Plantas Medicinales En Infusionesunclassified